RECOMBINANT LUMPY SKIN DISEASE VIRUS PROTEINS LSDV095 AND LSDV103 AS POTENTIAL ANTIGENS FOR DIFFERENTIAL DIAGNOSIS OF CAPRIPOXVIRUS INFECTIONS - Chervyakova , O.V.; Nissanova , R.K.; Shynybekova , G.; Tailakova , E.T.; Sultankulova , K.T.; Orynbayev , M.B. (Eurasian Journal of Applied Biotechnology, 2018)
Capripoxviruses cause infections in ruminants that are a significant threat to animal husbandry in many countries worldwide. Though the problem is sufficiently studied, to date there are no high-producing serological diagnostic tests available that can differentiate between capripoxvirus infections. To develop efficient serological tests, two recombinant lumpy skin disease virus proteins (LSDV095 and LSDV103) were expressed in Escherichia coli and purified using affinity chromatography. It was shown that both proteins were antigenically active against control sera, using western blotting and an indirect ELISA. As antigens, the recombinant proteins LSDV095 and LSDV103 detected antibodies only in the sera of animals infected with virulent capripoxvirus strains. The LSDV103 protein reacted only with the sera of animals infected with the virulent sheep pox and goat pox viruses. The results of this study allow the preliminary conclusion that the recombinant protein LSDV103 can be used for interspecies differentiation of capripoxvirus infections.